1967
DOI: 10.1037/h0020994
|View full text |Cite
|
Sign up to set email alerts
|

An abbreviation of the WISC for clinical use.

Abstract: Satz and Mogel (1962) and Mogel and Satz (1963) devised an abbreviated form of the Wechsler Adult Intelligence Scale (WAIS) which satisfied both clinical usefulness and validity. The procedure involved the selection of items (46%) from 9 of the 11 WAIS subtests, leaving Digit Span and Digit Symbol unchanged. The advantages of this type of short form were twofold: (a) all subtests were represented and (6) considerable time in administration was saved. High correlations between the abbreviated and standard forms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1968
1968
1985
1985

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Item sampling. A third approach is to sample items from some or all of the scales to produce a functionally representative test or a quasi "split-half" (Mogel & Satz, 1963;Pauker, 1963;Satz & Mogel, 1962;Satz, Van De Reit, & Mogel, 1967;Yudin, 1966). The use of only "starred" items in the administration of the S-B may also fall into this category (e.g., Birch, 1955;Wright, 1942).…”
Section: Methods Of Abbreviationmentioning
confidence: 99%
“…Item sampling. A third approach is to sample items from some or all of the scales to produce a functionally representative test or a quasi "split-half" (Mogel & Satz, 1963;Pauker, 1963;Satz & Mogel, 1962;Satz, Van De Reit, & Mogel, 1967;Yudin, 1966). The use of only "starred" items in the administration of the S-B may also fall into this category (e.g., Birch, 1955;Wright, 1942).…”
Section: Methods Of Abbreviationmentioning
confidence: 99%
“…Siniilarly, a validation study by Satz, Van de Riet, and Mogel (1967) supported Yudin's conclusion about the usefulness of the WISC short form. Silverstein (1968) concluded that the shortened form without the Yudin correction provided a satisfactory estimate of intelligence on the WAIS, WISC, and WPPSI.…”
mentioning
confidence: 61%
“…Some short form research with the Wechsler tests (no published research yet exists on short forms for the recently published WAIS-R) has focused on abbreviation by elimination of some test items (Mogel & Satz, 1963;Resnick, 1977;Satz, VanDeRiet, & Mogel, 1967;Yudin, 1966). The bulk of the research has focused on elimination of subtests.…”
Section: Oakland Counry Juvenile Courr Clinicmentioning
confidence: 99%